Oil and gas platforms degrade benthic invertebrate diversity and food web structure - Chen, Zelin; Cameron, Tom C.; Couce, Elena; Garcia, Clement; Hicks, Natalie; Thomas, Gareth E.; Thompson, Murray S.A.; Whitby, Corinne; O'Gorman, Eoin J. (The Science of the total environment, 2024)
Oil and gas exploitation introduces toxic contaminants such as hydrocarbons and heavy metals to the surrounding sediment, resulting in deleterious impacts on marine benthic communities. This study combines benthic monitoring data over a 30-year period in the North Sea with dietary information on >1400 taxa to quantify the effects of active oil and gas platforms on benthic food webs using a multiple before-after control-impact experiment. Contamination from oil and gas platforms caused declines in benthic food web complexity, community abundance, and biodiversity. Fewer trophic interactions and increased connectance indicated that the community became dominated by generalists adapting to alternative resources, leading to simpler but more connected food webs in contaminated environments. Decreased mean body mass, shorter food chains, and the dominance of small detritivores such as Capitella capitata near to structures suggested a disproportionate loss of larger organisms from higher trophic levels. These patterns were associated with concentrations of hydrocarbons and heavy metals that exceed OSPAR's guideline thresholds of sediment toxicity. This study provides new evidence to better quantify and manage the environmental consequences of oil and gas exploitation at sea. [Display omitted] •Causal links between hydrocarbon exploitation and ecological responses were studied.•Chemical and ecological effects were limited to within 500 m of the structure.•Elevated contamination leads to general defaunation but benefits opportunistic taxa.•Food webs are degraded through loss of larger predators and dietary specialists.•New evidence is provided for future monitoring practices to prioritize impact zones.